A hydrodynamic study of microbial polysaccharides considered for use in food and health products - Erten, Tayyibe (2016)
Microbial polysaccharides are widely used in many industrial and therapeutic applications as bioactive compounds, drug release and encapsulation materials for pharmaceuticals, and as natural ingredients or additives in food applications. To increase the utilisation or to improve for the food and healthcare applications of these polysaccharides, it is critical to have the detailed knowledge of macromolecular properties and interactions with other polymers. In this study, to properly understand the relationship between physical properties and functionality, the microbial polysaccharides-namely xanthan, gellan, microbial hyaluronic acid (HA) and schizophyllan, which have widely been used for many food and medical applications, were investigated. Taking advantage of recent advances in hydrodynamic techniques, including analytical ultracentrifugation (AUC) based on sedimentation velocity and equilibrium, size exclusion chromatography coupled to multi angle light scattering (SEC-MALS) and viscometry, the solution properties of these polysaccharides were studied. Since conformation analyses are important for macromolecular structure function relationships, the conformation of these microbial polysaccharides were examined using the accomplished method-Multi-HYDFIT. For schizophyllan and gellan, the samples were depolymerised using heat treatment to estimate the conformation. The results indicated that, the three microbial polysaccharides (xanthan, gellan, schizophyllan) adapted the rigid rod conformation whereas another polysaccharide-microbial HA adapted semi-flexible coil structure. Then, the possible interactions of these polysaccharides were investigated with chitosan of different degrees of acetylation using the principle of co-sedimentation in AUC. Xanthan-chitosan mixture presented strong evidence by proving a clear interaction on the basis of changes in the distribution of sedimentation coefficients in the solution form of mixture whereas the mixture of chitosan schizophyllan and chitosan-HA did not show or prove any clear interactions at studied concentrations and solution conditions.